Microbial Spoilage of Bakery Products and Its Control by Preservatives - Saranraj, P (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Spoiled food may be defined as a food that has been damaged or injured so as to make it undesirable for human consumption. Bakery products are an important part of a balanced diet and a wide variety of such products can be found on supermarket shelves. However, bakery products, like many processed foods, are subject to physical, chemical and microbiological spoilage. While physical and chemical spoilage limits the shelf life of low and intermediate moisture bakery products, microbiological spoilage by bacteria, yeast and molds is the concern in high moisture products. Many industrially produced baked goods emerge from the baking process with a surface that is essentially sterile but post bake handling can quickly lead to fungal, microbial surface contamination as a result of exposure to airborne contaminants as well as equipment contact. This present review is focused on the microbial spoilage of bakery products and its control by preservatives. This review assesses the following topics: economical importance of bakery products, microbial spoilage of bakery products, physical factors affecting microbial growth, control of microbial growth in bakery products by using chemical preservatives and biopreservatives.